Author and Text Interpretation: F. Scott Fitzgerald and the Great Gatsby - Muradian, Gaiane; Antonyan, Zaruhi (Bulletin of Yerevan University B: Philology, 2025)
To fully understand a literary work, we must explore its origins – who wrote it, when and why it was created, and the meanings the author intended to convey. In The Great Gatsby (1925), F. Scott Fitzgerald’s personal views, emotions, and thoughts are deeply embedded in the novel’s structure and themes. Therefore, to interpret the novel more effectively, we need to consider these influences and how they shape Fitzgerald’s stylistic and linguistic choices. This analysis will examine Fitzgerald’s narrative techniques, including first-person and retrospective narration, as well as his use of language to establish tone and meaning. Through the linguo-stylistic method of analysis, we will explore his figurative language such as metaphors, similes and other literary tools to uncover deeper layers of expression. Additionally, a cognitive-stylistic approach will help us understand how Fitzgerald’s language choices evoke emotions in characters and influence the reader’s perception of the novel’s themes.